Pertanggungjawaban Hukum Pejabat Pemerintahan Atas Penyelenggaraan Pengelolaan Sampah Yang Tidak Memenuhi Norma, Standar, Prosedur, Dan Kriteria (NSPK) - Kurdi Kurdi (JUNCTO: Jurnal Ilmiah Hukum, 2026)
This study examines the legal accountability of government officials for failures in waste management, particularly the operation of final disposal sites (landfills) employing the open dumping system in violation of the established Norms, Standards, Procedures, and Criteria (NSPK). Using a normative juridical method with statutory and conceptual approaches, the research analyzes the boundaries between official liability (fautes de service) and personal liability (fautes personnelles) of public officials. The findings indicate that public officials may incur personal liability when they are proven to have committed gross negligence, abuse of authority, or violations of the General Principles of Good Governance (AUPB) in disregarding the imperative prohibition of the open dumping system. Furthermore, the NSPK framework functions as a technical–juridical parameter (standard of care) in assessing the elements of unlawful acts committed by public authorities (Onrechtmatige Overheidsdaad). Systemic disregard of NSPK constitutes a form of maladministration that infringes upon citizens’ constitutional right to a good and healthy environment. Strengthening oversight mechanisms and ensuring consistent enforcement of sanctions are therefore essential to secure governmental compliance with national waste management standards.